RACISM IN TONI MORRISON’S THE BLUEST EYE - Thesalonika G P Kumaunang; Tini Mogea; Olga Rorintulus (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The purpose of this study is to reveal the form of racism and its impact on the mental health of African American in Toni Morrison's The Bluest Eye. The design of this study is qualitative research because the data that support this research are collected from books, journals, articles, and internet. The researchers use two kinds of data collection, namely the primary source that is the novel itself and the secondary sources are books, articles, the internet, and journals. The approach needed in research is mimetic approach, because this topic is related to the environment and as a reflection of human life. The author right to see racism in historical background of the novel. In analysing the data, researchers use three techniques called data reducing, data display, and conclusion. Researchers have read the novel and then decided the topic. From the amount of data collected from various sources researchers use text or jotting to compares, contrasts, and sorts the required data, from the notes written by the researchers, then can categorize the relevant data. The results of the analysis are racism experienced by African Americans in the form of rejection, insults and violence. Racism in the novel is not only practiced by white people but also among black people. Racism can cause victims to hate themselves, and hate others. By the story of the novel and the result of the analysis, researchers find that this impact is particularly vulnerable to children and women.